The Effect of Briks Walking Exercise on Blood Pressure Reduction in Hypertensive Patients in the Working Area of the Hative Kecil Health Center in 2021 - Lesnusssa, Dessy K.; Thalib, Abdul; Latuamury, Sitti R (Innovative Approaches in Health Science Journal, 2024)
Background: Hypertension is a serious health problem that is increasing globally. Brisk Walking Exercise is one of the non-pharmacological therapies that is effective in lowering blood pressure in hypertensive patients. This study aims to evaluate the effect of Brisk Walking Exercise on blood pressure in people with hypertension in the Working Area of the Hative Kecil Health Center in 2021. Medical record and interview data were used to understand the benefits of Brisk Walking Exercise in treating hypertension in the community. Methods : This study used a pre-experimental method with one pretest-posttest group, conducted in the Working Area of the Small Hative Health Center in November 2021 with 23 respondents selected using non-probability sampling techniques. Results: The results of data analysis using SPSS with Wilcoxon test showed a value of p = 0.000, there was a significant effect of brisk walking exercise on reducing blood pressure in hypertensive patients in the Working Area of the Hative Kecil Health Center. Conclusion: The difference in values between before and after the administration of brix walking exercise showed a positive effect of the intervention on blood pressure in hypertensive patients in the region.